The challenges and lessons from a formative process and value-based evaluation of the wave 1 roll-out of the all Wales Diabetes Prevention Programme - Sharon Parsons (BMC Public Health, 2024)
BackgroundThe All Wales Diabetes Prevention Programme (AWDPP) is a Wales wide, public health initiative designed to systematically identify adults at risk of developing type 2 diabetes and offer a 30-minute person-centred lifestyle conversation focused on diet and physical activity. An independent formative process and value-based evaluation was commissioned to examine the implementation of this programme in 14 primary care cluster areas across Wales during the initial roll-out.MethodsThis evaluation was undertaken to ascertain the views on early implementation of the programme from service users, health care professionals and key stakeholders. The evaluation was informed by the Medical Research Council Framework for Process Evaluation and Wales Prudent Healthcare principles. As part of the value-based assessment, a preliminary cost-consequence analysis was conducted to understand the short-term economic impact of the implementation of the programme.ResultsService users who took part in the evaluation highly valued the programme and nearly half had been previously unaware that they were at risk of developing type 2 diabetes. Delivering the programme presented challenges but there was significant enthusiasm and support from all stakeholders. Overall, the programme was being delivered as intended albeit with evidence of some variation in the application of the programme eligibility criteria.ConclusionsIn Wave 1 of the AWDPP roll-out, the intent to deliver the programme in line with Prudent Healthcare was successful and promising in terms of demonstrating value. Opinions expressed by service users suggest the AWDPP matters to them; raising awareness, promoting knowledge and capacity to change behaviours and motivate and raise confidence.